McGraw-Hill machining and metalworking handbook - Walsh, Ronald A. (McGraw-Hill, 1994)
Aims to provide accurate information on the modern techniques and procedures essential to achieving high quality machining and metalworking. It covers practical topics - from safety procedures and the latest ANSI standards, to the latest metal-cutting practices and the newest polishing compounds.